Mind the gap: The difference between U.S. and European loan rates - Tobias Berg; Anthony Saunders; Sascha Steffen; Daniel Streitz (Zentrum für Europäische Wirtschaftsforschung (ZEW), 2016)
We analyze differences in the pricing of syndicated loans between U.S. and European loans. For credit lines, U.S. borrowers pay significantly higher spreads, but also lower fees, resulting in similar total costs of borrowing in both markets. For term loans, U.S. firms pay significantly higher spreads. While European firms across the rating spectrum issue terms loans, only low quality U.S. firms rely on term loans. U.S. issuers perform worse after loan origination compared to European issuers, which explains 30% of the spread differential. Increasing loan supply by institutional lenders in the U.S. since 2003 eventually fully removed the term loan pricing gap.
urn:nbn:de:bsz:180-madoc-407975
Keywords: G30; G20; G15; 330; loans; corporate debt; fees; market integration; globalization